Real-time optical vascular imaging: a method to assess the microvascular circulation of myofascial free flaps used in the head and neck region. Issue 5 (May 2020) - Bastos, P.; Fry, A.; Cascarini, L.; Yeung, E.; Cook, R.
Abstract: Microvascular free flaps are considered the gold standard in head and neck reconstructive surgery. Myofascial flaps, in particular, are useful in certain oral and maxillofacial reconstruction cases, where mucosal regeneration over the transplanted tissue is planned. Despite high success rates, 1–6% of free flaps fail. A plethora of methods are available to assess transplanted tissue viability after reconstruction, including clinical observational monitoring, surface Doppler, implantable Doppler probe, colour Doppler sonography, laser Doppler flowmeter, surface temperature and indocyanine green angiography. However, no method has demonstrated adequate reliability or has proven to be cost-effective. The authors tested a technique called real-time optical vascular imaging to evaluate the microvascular circulation of myofascial free flaps. This technique was develop at Guy's Hospital, London to observe the microvascular anatomy of the oral cavity in vivo, non-invasively and without the need for patient preparation, with the aim of detecting and monitoring oral diseases. This technology detects the red blood cells flowing inside the microvasculature at a depth of approximately 2 mm, allowing the microvascular architecture and blood flow to be determined. This study showed that RTOVI may prove to be beneficial for the early detection of vascular compromise due to its immediacy and the feasibility of assessing multiple graft tissue regions.